THE ROLE OF PERCEIVED ORGANIZATIONAL SUPPORT AND PROFESSIONAL IDENTITY IN PREDICTING HAPPINESS AT WORK AMONG EMPLOYEES OF MULTINATIONAL COMMUNICATION CONSULTING FIRMS IN JAKARTA - Asrini Mahdia (Penelitian dan Pengembangan Ilmu, 2026)
This study examines the influence of Perceived Organizational Support (POS) and Professional Identity on Happiness at Work among employees of multinational communication consulting firms in Jakarta. Happiness at Work is conceptualized as a multidimensional construct encompassing hedonic well-being, engagement, and positive affect experienced within the occupational context. Drawing on Social Exchange Theory (Blau, 1964) and Social Identity Theory (Tajfel & Turner, 1979), this study proposes that employees who perceive strong organizational support and possess a robust professional identity will report higher levels of happiness at work. A quantitative correlational design was employed with a sample of 100 employees selected through purposive sampling. Data were collected using validated Likert-scale instruments and analyzed via Pearson correlation and multiple regression in SPSS. Results indicated that both POS (r = .612, p < .01) and Professional Identity (r = .673, p < .01) were significantly and positively correlated with Happiness at Work. The regression model explained 56.4% of the variance in Happiness at Work (R² = .564). These findings underscore the critical role of organizational and identity-based resources in fostering employee well-being in the high-demand environment of the communications consulting industry.